2017
DOI: 10.1042/bcj20161022
|View full text |Cite
|
Sign up to set email alerts
|

Interaction studies between periplasmic cytochromes provide insights into extracellular electron transfer pathways ofGeobacter sulfurreducens

Abstract: bacteria usually prevail among other microorganisms in soils and sediments where Fe(III) reduction has a central role. This reduction is achieved by extracellular electron transfer (EET), where the electrons are exported from the interior of the cell to the surrounding environment. Periplasmic cytochromes play an important role in establishing an interface between inner and outer membrane electron transfer components. In addition, periplasmic cytochromes, in particular nanowire cytochromes that contain at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Periplasmic and transmembrane electron relays are more diverse in species. Five proteins of the PpcA family and GSU1996 in periplasm are found to shuttle electrons from the cytoplasmic cyt c to downstream cyt clusters in the envelope (Dantas et al, ; Fernandes, Nunes, Paquete, & Salgueiro, ). Transmembrane electron flow across the envelope relies on cyt clusters such as OmaB–OmcB, OmaC–OmcC, extA–extC/D, and extG–extF, each of which is integrated with a porin for protein localization (Otero, Chan, & Bond, ; Shi et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periplasmic and transmembrane electron relays are more diverse in species. Five proteins of the PpcA family and GSU1996 in periplasm are found to shuttle electrons from the cytoplasmic cyt c to downstream cyt clusters in the envelope (Dantas et al, ; Fernandes, Nunes, Paquete, & Salgueiro, ). Transmembrane electron flow across the envelope relies on cyt clusters such as OmaB–OmcB, OmaC–OmcC, extA–extC/D, and extG–extF, each of which is integrated with a porin for protein localization (Otero, Chan, & Bond, ; Shi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Periplasmic and transmembrane electron relays are more diverse in species. Five proteins of the PpcA family and GSU1996 in periplasm are found to shuttle electrons from the cytoplasmic cyt c to downstream cyt clusters in the envelope Fernandes, Nunes, Paquete, & Salgueiro, 2017).…”
mentioning
confidence: 99%
“…Several studies have focused on elucidating the role of c-type cytochromes in electron transport and storage. Esteve-Núñez and coworkers developed a fluorescence technique to measure the redox status of c-type cytochromes to evaluate their capacity [37], while Fernandes and coworkers used NMR to study periplasmic cytochromes [38]. Capacitance and storage in redox components of EABs on cathodes has, to the best of our knowledge, not been studied.…”
Section: Storage Mechanisms In Eabsmentioning
confidence: 99%
“…Several different types of c‐type cytochromes are at play: Some can act as electron carriers in the outer membrane with, e.g., 12 heme units, while others are smaller, e.g., with three heme units, acting as electron shuttles in the periplasm. Yet, the exact interplay between them [ 145 ] and electron flow within each cytochrome [ 146 ] is still under investigation. It has also been reported that small monoheme c‐type cytochromes are excreted by G. sulfurreducens and might participate in the bioreduction of Fe 3+ or transfer electrons to partner bacteria.…”
Section: Mechanisms Of Microbial Synthesis Of Nanoparticlesmentioning
confidence: 99%